The Role of Ascending Ventral‐Tegmental Fibers for Recovery after Stroke. Issue 5 (16th January 2023) - Hosp, Jonas A.; Dressing, Andrea; Engesser, Anika; Glauche, Volkmar; Kümmerer, Dorothee; Vaidelyte, Ema B.; Musso, Mariachristina; Rijntjes, Michel; Weiller, Cornelius
Abstract : Objectives: The integrity of cortical motor networks and their descending effector pathway (the corticospinal tract [CST]) is a major determinant motor recovery after stroke. However, this view neglects the importance of ascending tracts and their modulatory effects on cortical physiology. Here, we explore the role of such a tract that connects dopaminergic ventral tegmental midbrain nuclei to the motor cortex (the VTMC tract) for post‐stroke recovery. Methods: Lesion data and diffusivity parameters (fractional anisotropy) of the ipsi‐ and contralesional VTMC tract and CST were obtained from 133 patients (63.9 ± 13.4 years, 45 women) during the acute and chronic stage after the first ever ischemic stroke in the middle cerebral artery territory. Degeneration of VTMC tract and CST was quantified and related to clinical outcome parameters (National Institute of Health Stroke Scale with motor and cortical symptom subscores; modified Fugl‐Meyer upper extremity score; modified Ranking Scale [mRS]). Results: A significant post‐stroke degeneration occurred in both tracts, but only VTMC degeneration was associated with lesion size. Using multiple regression models, we dissected the impact of particular tracts on recovery: Changes in VTMC tract integrity were stronger associated with independence in daily activities (mRS), upper limb motor impairment (modified Fugl‐Meyer upper extremity score) and cortical symptoms (aphasia, neglect) captured by National Institute of Health Stroke Scale compared to CST. Changes in CST integrity merely were associated with the degree of hemiparesis (National Institute of Health Stroke Scale motor subscale). Interpretation: Post‐stroke outcome is influenced by ascending (VTMC) and descending (CST) fiber tracts. Favorable outcome regarding independence (modified Ranking Scale), upper limb motor function (modified Fugl‐Meyer upper extremity score), and cortical symptoms (aphasia, neglect) was more strongly related to the ascending than descending tract. ANN NEUROL 2023;93:922–933